2015
DOI: 10.1002/pros.22989
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular profiling of ETS and non‐ETS aberrations in prostate cancer patients from northern India

Abstract: BACKGROUNDMolecular stratification of prostate cancer (PCa) based on genetic aberrations including ETS or RAF gene‐rearrangements, PTEN deletion, and SPINK1 over‐expression show clear prognostic and diagnostic utility. Gene rearrangements involving ETS transcription factors are frequent pathogenetic somatic events observed in PCa. Incidence of ETS rearrangements in Caucasian PCa patients has been reported, however, occurrence in Indian population is largely unknown. The aim of this study was to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…SPINK1/TATI is known to be produced in the prostate and in prostate cancer, and its production increases with a higher tumor grade . Strongly increased SPINK1 expression is found in about 10% of all prostate cancers, and serum concentrations of SPINK1 are increased in more than 40% of patients with advanced prostate cancer . Increased SPINK1/TATI expression was observed in our cancer groups compared to controls (normals).…”
Section: Discussionmentioning
confidence: 54%
“…SPINK1/TATI is known to be produced in the prostate and in prostate cancer, and its production increases with a higher tumor grade . Strongly increased SPINK1 expression is found in about 10% of all prostate cancers, and serum concentrations of SPINK1 are increased in more than 40% of patients with advanced prostate cancer . Increased SPINK1/TATI expression was observed in our cancer groups compared to controls (normals).…”
Section: Discussionmentioning
confidence: 54%
“…Clinical specimens were collected after obtaining written informed consent from the patients and Institutional Review Board approvals from the King George's Medical University, Lucknow and Indian Institute of Technology, Kanpur, India. A total of 20 PCa specimens were selected for this study based on the SPINK1 and TMPRSS2-ERG status, confirmed by qPCR, immunohistochemistry and Fluorescent in situ hybridization (FISH) for gene rearrangement (64). The PCa specimens used in this study were collected from men who underwent needle core biopsies and transurethral resection of the prostate (TURP) to relieve obstructive symptoms from locally advanced disease between year 2014 and 2016.…”
Section: Human Prostate Cancer Specimensmentioning
confidence: 99%
“…Majority of the PCa patients harbor gene rearrangements between members of the ETS transcription factor family and the androgen-regulated transmembrane protease serine 2 (TMPRSS2), most recurrent (~50%) being TMPRSS2-ERG, a gene fusion involving the v-ets erythroblastosis virus E26 oncogene homolog (ERG) (5,7). The ERG transcription factor encoded by TMPRSS2-ERG fusion is known to drive cell invasion and metastases, induce DNA damage in vitro, and focal pre-cancerous prostatic intraepithelial neoplasia (PIN) lesions in transgenic mice (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of ERG-positive tumors in our study (26%) is similar to that in the study by Rawal et al 22 who have reported a low frequency; eight cases were ERG positive (27%) by FISH in a total cohort of 30 samples from a single medical institution in North India. However, Ateeq et al 23 detected ERG overexpression by IHC in 46 of 94 (48.9%) PCa cases from northern India; this was subsequently confirmed in a much smaller subset (17 samples) by FISH.…”
Section: Discussionmentioning
confidence: 96%